PENDAMPINGAN UMKM MIE AYAM PODO MAMPIR DALAM MENINGKATKAN PENDAPATAN LABA PENGHASILAN MELALUI RENCANA PEMASARAN DAN PEMANFAATAN MEDIA SOSIAL - Ningsih, Ati’ Lia; Wahyuni, Endang Sri; Fithriyah, Nuzulia (Universitas Al-Amien Prenduan, 2023)
The purpose of this service activity is to provide understanding, delivery and training to Mie Ayam business partners in aspects of marketing planning through digital marketing social media so as to increase their income. This mentoring activity was carried out by IDIA Prenduan students, Faculty of Economics and Islamic Business, Sharia Economics study program which has four stages of implementation, namely preparation and planning, implementation, evaluation and monitoring. This stage ensures that the objectives, targets, and outcomes of the program are achieved. This activity is carried out using participatory methods such as observation, interviews, focus group discussions, and joint decision making. The result of the series of 4 stages is an increase in business income of Podo Stopped Chicken Noodles, improved the quality of the taste of Podo Mampir Chicken Noodles marketed, and increased marketing of quality goods products.